Analysis of voice disorders at Shree Birendra Hospital - Karki, Reeba; Rai, Kiran (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: Voice disorder is a common condition encountered in ENT-HNS clinic. This study was conducted to analyze the prevalence, presentation and to assess the management of patients with voice disorders at Shree Birendra Hospital. Method: A prospective study of all the patients with voice disorders attending in ENT-HNS outpatient department of Shree Birendra Hospital from November 15th 2010 to May 15th 2011 were evaluated both clinically and with fi bro optic laryngoscope. Each patient was assessed by consultant ENT-Head and Neck surgeon and speech therapist. Patient with psychological disorders and those without fi bro optic laryngoscope findings were excluded in the study. Results: Total numbers of 120 patients were analyzed. There were 88(73%) females and 32 (27%) males. Most common voice disorder was habitual dysphonia among 70 patients (58.3%) followed by true vocal cord nodule in 20 patients (16.6%). Majority of the patients (79.16%) with voice disorders were managed by speech therapy and only 25 (21%) patients required surgical intervention. Conclusion: Voice disorders are frequent occurrence and most of these can be treated with voice therapy alone. Only few require surgical intervention. DOI: http://dx.doi.org/10.3126/mjsbh.v10i2.6455 Medical Journal of Shree Birendra Hospital July-Dec 2011 10(2) 8-10